2021
DOI: 10.3390/plants10102121
|View full text |Cite
|
Sign up to set email alerts
|

Isohydricity of Two Different Citrus Species under Deficit Irrigation and Reclaimed Water Conditions

Abstract: Citrus species are frequently subjected to water and saline stresses worldwide. We evaluated the effects of diurnal changes in the evaporative demands and soil water contents on the plant physiology of grapefruit and mandarin crops under saline reclaimed (RW) and transfer (TW) water conditions, combined with two irrigation strategies, fully irrigated (fI) and non-irrigated (nI). The physiological responses were different depending on the species. Grapefruit showed an isohydric pattern, which restricted the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 93 publications
1
7
0
Order By: Relevance
“…The underestimation of Ψ stem made by the MT could limit its use in those deficit irrigation strategies in which the Ψ stem threshold value selected to irrigate the trees is −2.0 Mpa. Ψ stem values below −2.0 Mpa have been broadly reported in experiments with olive trees [43], citrus [44], and almond trees [36] under deficit irrigation strategies. On the other hand, in fruit trees such as pears, apples, cherries, peaches, and nectarines, Ψ stem values below −2.0 MPa are considered severe water stress and are undesirable as they will have a negative effect on current year fruit quality or yield or fruit quality the next year [45].…”
Section: Discussionmentioning
confidence: 80%
“…The underestimation of Ψ stem made by the MT could limit its use in those deficit irrigation strategies in which the Ψ stem threshold value selected to irrigate the trees is −2.0 Mpa. Ψ stem values below −2.0 Mpa have been broadly reported in experiments with olive trees [43], citrus [44], and almond trees [36] under deficit irrigation strategies. On the other hand, in fruit trees such as pears, apples, cherries, peaches, and nectarines, Ψ stem values below −2.0 MPa are considered severe water stress and are undesirable as they will have a negative effect on current year fruit quality or yield or fruit quality the next year [45].…”
Section: Discussionmentioning
confidence: 80%
“…Ψstem of Salvia officinalis consequence of the salinity of this water source (Lorente et al, 2022). The same trend observed Romero-Trigueros et al (2021a) in grapefruit trees irrigated with RW.…”
Section: Reclaimed Watersupporting
confidence: 66%
“…Citrus species Romero-Trigueros et al, 2021a). In olive trees, it was reported that it is possible to schedule irrigation from automated estimations of gs, ensuring an adequate soil water status and avoiding any hard effect on olive yields .…”
Section: And Inmentioning
confidence: 99%
“…The sensitivity of g s to PWS changes was shown to be a good irrigation indicator for several crops [32,157,158]. It was studied in the application of an irrigation schedule in olives [159], grapefruit [160], and grapevines [161], among many others.…”
Section: Stomatal Conductancementioning
confidence: 99%
“…In chestnut, LWP was used to assess water transpiration [193], and SWP was used as an indicator for smart irrigation [194]. In pistachio, SWP was considered a tool to manage an irrigation schedule [117], whereas, on the contrary, the isohydric behavior of grapefruit limited the use of SWP as an indicator of plant water status [160]. In cherry, Blanco [35,195] showed that SWP was the most reliable and stable water stress indicator compared to other physiological variables as it clearly detected irrigation changes and quantified water status.…”
Section: Water Potentialmentioning
confidence: 99%